Comparative analysis of lingual bracket transfer accuracy using fully versus partially enclosed 3D-printed indirect bonding trays: an in vivo study - Nguyen, Viet Anh (PeerJ, 2025)
Background Lingual orthodontic treatment requires precise bracket positioning to ensure optimal outcomes. This study aimed to compare the transfer accuracy of fully enclosed (FE) and partially enclosed (PE) three-dimensionally (3D) printed indirect bonding trays for lingual brackets, focusing on linear and angular errors, and to evaluate their clinical applicability. Materials and Methods A total of 20 patients with 498 brackets bonded on both arches were included in this in vivo study. Two tray designs—FE and PE—were fabricated using a standardized digital workflow and 3D-printed with rigid resin. Bracket transfer accuracy was assessed by superimposing post-bonding scans with planned virtual models. Linear (mesiodistal, buccolingual, occlusogingival) and angular (rotation, angulation, torque) errors were measured. Statistical analyses included t-tests to compare transfer accuracy between the two tray designs. Results Both tray designs achieved clinically acceptable linear accuracy, with errors below 0.5 mm across all dimensions. Angular errors for rotation and angulation were also within clinically acceptable limits of 2°, but torque transfer remains a challenge for both tray designs. The PE design showed significantly lower buccolingual and occlusogingival errors for premolars and the total sample, while the FE design demonstrated significantly lower torque errors for molars. However, the FE design required longer bonding times (84.2 ± 14.5 min) compared to the PE design (70.7 ± 12.8 min, p = 0.041), without offering a significant overall accuracy advantage. Conclusion The PE tray design is the preferred option over the FE design for its simplicity and accuracy. Torque errors in the PE design can be mitigated with supplementary stabilization materials.
Keywords: 3D-printed indirect bonding trays; Lingual orthodontics; Bracket transfer accuracy; Fully enclosed design; Partially enclosed design